The Staffordshire Hoard. An Anglo-Saxon Treasure - Fern, Chris; Dickinson, Tania; Webster, Leslie (Reports of the Research Committee of the Society of Antiquaries of London, 2019)
The Staffordshire Hoard: An Anglo-Saxon Treasure tells the story of the Staffordshire Hoard's discovery and acquisition, and the six-year research project that pieced its fragments back together, identified its objects and explored their manufacture. Key chapters discuss the decoration and meaning of the Hoard's intricate ornament, the techniques of Anglo-Saxon craftsmen, the religious and historical background, and hoarding practice in Britain and Europe, to place this most exceptional find in context. Finally, the text explores the impact that the find has had locally, nationally and internationally in the twenty-first century.